Paraneoplastic Hyperleukocytosis in Pancreatic Adenocarcinoma - Wu, Evan S. (J Pancreat Cancer, 2017)
Background: Paraneoplastic hyperleukocytosis is a rare phenomenon observed in patients with adenocarcinomas and other malignancies. In this study, we present a case of paraneoplastic hyperleukocytosis in pancreatic adenocarcinoma secondary to excessive secretion of serum granulocyte colony-stimulating factor (G-CSF). Presentation: We report a 71-year-old Caucasian male who presented to our hospital with hyperleukocytosis in the setting of locally advanced pancreatic adenocarcinoma. The patient was recently diagnosed 4 months before presentation and received abraxane/gemcitabine in addition to palliative radiation therapy for continued gastrointestinal bleeding. During routine laboratory assessment, the patient was found to have a white blood cell (WBC) count of 153 K/UL (75% neutrophils and 14% bands). Bone marrow biopsy and cytology were negative for neoplastic features. Serum G-CSF levels returned markedly elevated, supporting the diagnosis of paraneoplastic hyperleukocytosis. Interestingly, the WBC count decreased significantly following each of two cycles of chemotherapy, further suggesting a paraneoplastic etiology of hyperleukocytosis. The patient did not receive any growth factor support at any point before or during treatment. Conclusion: In conclusion, the presence of hyperleukocytosis in cancer should raise clinical suspicion of a paraneoplastic phenomenon when other possible causes have been excluded. Hyperleukocytosis in this setting may correlate with progression of disease and lessen with treatment.